2015
DOI: 10.15850/amj.v2n2.565
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Knowledge among Treatment Supporter of Children Patients with Tuberculosis at Lung Clinic Bandung October–November 2012

Abstract: Background: Children are the most vulnerable to get TB infection and infected by adult patients. One of the components of Directly Observed Treatment Short Course (DOTS) is direct observation by treatment supporter who has important role in the success of TB's treatment. The aim of this study was to identify the characteristics and knowledge among treatment supporter of children patients with TB at Lung Clinic Bandung. Methods: A descriptive study was conducted in October-November 2012 to 96 treatment supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This finding that most TB treatment supporters are female is consistent with previous reports from Bandung (84.4%) and Depok (91.8%) in West Java Indonesia. [ 10 13 ] Perhaps the cultural factors in most patriarchal societies that attribute responsibilities of providing care to females could contribute to women taking on this role. [ 14 15 ] Further, the extended family support systems in sub-Saharan Africa which usually rely on family members to provide care for the sick may partly account for the higher proportion of family members serving as treatment supporters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding that most TB treatment supporters are female is consistent with previous reports from Bandung (84.4%) and Depok (91.8%) in West Java Indonesia. [ 10 13 ] Perhaps the cultural factors in most patriarchal societies that attribute responsibilities of providing care to females could contribute to women taking on this role. [ 14 15 ] Further, the extended family support systems in sub-Saharan Africa which usually rely on family members to provide care for the sick may partly account for the higher proportion of family members serving as treatment supporters.…”
Section: Discussionmentioning
confidence: 99%
“…Coughing and sneezing by patients with TB and sharing dishes with patients were the most frequently reported modes of transmission in several other studies. [ 13 30 31 32 ] Some respondents had incorrect knowledge about transmission such as through smoking, use of herbal concoctions, and inhalation of dust. This is an indication that gaps in knowledge of TB transmission still exist.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge and perception about TB can influence care-seeking behavior and adherence to treatment [15][16] The previous studies have showed that there are many parents who do not have good knowledge of TB. A research conducted by Suhada et al (2015) states that there are still many parents who do not know how long TB treatment is and some respondents do not know that drugs for TB have to be consumed every day for 6 months. However 50% of the respondents know the impact of incomplete adherence to the treatment [17].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 49.3% of the respondents ahve heard about TB in children and 94.8% of the respondents know that TB is contagious. In addition, the majority of the respondents (85.3%) knows that cough is the symptoms of TB and only a few of them know the other symptoms of TB [18].…”
Section: Discussionmentioning
confidence: 99%